2009
DOI: 10.1016/j.yhbeh.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Social closeness increases salivary progesterone in humans

Abstract: We examined whether interpersonal closeness increases salivary progesterone. One hundred and sixty female college students (80 dyads) were randomly assigned to participate in either a closeness task with a partner versus a neutral task with a partner. Those exposed to the closeness induction had higher levels of progesterone relative to those exposed to the neutral task. Across conditions, progesterone increase one week later predicted the willingness to sacrifice for the partner. These results are discussed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 24 publications
(37 reference statements)
2
96
1
1
Order By: Relevance
“…In a repeated-measures study of women, Miller (2011) found that attention to social stimuli both increased during the high-progesterone phase of the menstrual cycle and was correlated with salivary progesterone. Brown et al (2009) found that women engaging in a task promoting social closeness showed increases in progesterone, and the extent of this increase predicted altruistic motivation in participants towards their task partner one week later. In both men and women, following the experience of experimental social rejection, progesterone increased when participants were told that they would have an opportunity to affiliate with others (Maner, Miller, Schmidt, & Eckel, 2010).…”
Section: Progesteronementioning
confidence: 93%
“…In a repeated-measures study of women, Miller (2011) found that attention to social stimuli both increased during the high-progesterone phase of the menstrual cycle and was correlated with salivary progesterone. Brown et al (2009) found that women engaging in a task promoting social closeness showed increases in progesterone, and the extent of this increase predicted altruistic motivation in participants towards their task partner one week later. In both men and women, following the experience of experimental social rejection, progesterone increased when participants were told that they would have an opportunity to affiliate with others (Maner, Miller, Schmidt, & Eckel, 2010).…”
Section: Progesteronementioning
confidence: 93%
“…In addition to cortisol, there is a growing body of literature linking progesterone levels/responses to both stress and to affiliation and rejection ( Brown et al , 2009; Childs et al , 2010; Gettler et al , 2013; Maner et al , 2010; Schultheiss et al , 2003; Schultheiss et al , 2004; Wirth & Schultheiss, 2006; Wirth et al , 2007; Wirth, 2011). Progesterone is not only a gonadal hormone, but is also produced in the adrenal glands, and progesterone levels increase in response to pharmacological stimulation of the HPA axis ( Genazzani et al , 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Study 1 revealed that only in the agency vision condition were increases in power motive imagery accompanied by increases in testosterone, a hormonal indicator of implicit power motivation (e.g., Brown et al, 2009;Schultheiss et al, 2004;Wirth & Schultheiss, 2004). In the affiliation vision condition, changes in affiliation imagery were associated with progesterone changes, a hormonal indicator of implicit affiliation motivation (Schultheiss et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…shown that the arousal of n Power (e.g., via winning a competition or watching power-thematic film segments) is associated with increasing salivary testosterone levels, whereas the arousal of n Affiliation (e.g., via film affiliation-thematic segments or via social closeness) is associated with increasing salivary progesterone levels (Brown, Fredrickson, Wirth, et al, 2009;Schultheiss et al, 2004;Wirth & Schultheiss, 2006). Therefore, we hypothesized that in the affiliation vision condition, changes in affiliation imagery would be associated with changes in salivary progesterone, while in the agency vision condition, changes in power 3 imagery would be associated with changes in salivary testosterone.…”
Section: Progesteronementioning
confidence: 98%